"Do chão do quilombo" Ilha São Vicente - TO: - Santos, Luziane Laurindo dos (Universidade Federal do Tocantins, 2023)
This thesis has as its theme the teaching of the school subject of history outside school grounds as a strategy to empower and value local history, give visibility to the quilombola community and favor, thus, learning of local history. It is a qualitative research, based upon oral history, and, more specifically, thematic oral history. The techniques performed were bibliographical and documental research, fieldwork and surveys. The main objective was to analyze the practice developed in history lessons, within the scope of the project “Quilombo a sacred territory, in focus: Quilombo Ilha São Vicente”, in State School Denise Gomide Amui’s high school classes, in Araguatins/TO, between September and November from 2019. This was further developed alongside the quilombola community, in the timeframe between October and November from the year 2019. During the practice there were trips to the quilombo, with the development of activities that encompassed this territory’s history and its memories, relating these to the history of that Tocantins municipality, aiming to thus demonstrate to both students and teachers that it is possible, and necessary, the meshing of knowledge and the valuing and inclusion of local history as a strategy of decolonial teaching. The practice assessment was undergone through thematic surveys with participants (students, teachers, pedagogical staff and quilombola community). In the assessment, oralities point to a positive sign regarding the practice, as it